2010
DOI: 10.1192/pb.bp.106.011510
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of group-based cognitive–behavioural therapy in patients with obsessive–compulsive disorder

Abstract: Exposure and response prevention (ERP) is the behavioural treatment of choice for obsessive-compulsive disorder (OCD).1 Many early studies showed 70-75% improvement after 15 sessions of ERP, 2,3 but later studies showed positive gains from cognitive approaches aimed at reducing obsessions and rituals. Several cognitive models have been proposed for OCD, including those of Salkovskis 4 and Rachman. 5 Rachman suggests that obsessions are caused by catastrophic misinterpretation of the significance of one's thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In long term consequences one study found that in 2-years follow-up, patients pretended the improvements on OCD (which was the reduction in symptoms) after getting CBT (Whittal et al, 2008), another study found the effects of CBT on OCD pretended on a 5-year follow-up (Oppen et al, 2005), and similar results were also shown in internet-based CBT with a 2 year follow-up (Andersson et al, 2014). The positive effect of CBT on obsessions and compulsions does not only remain at the individual level, but also in group therapies (Kearns et al, 2010;Safak et al, 2014), which is also shown in follow-up sessions (Haland et al, 2010). In the case of religious OCD, Abramowitz (2001) found a positive effect of ERP and/or cognitive intervention on religious OCD.…”
Section: Discussionmentioning
confidence: 79%
“…In long term consequences one study found that in 2-years follow-up, patients pretended the improvements on OCD (which was the reduction in symptoms) after getting CBT (Whittal et al, 2008), another study found the effects of CBT on OCD pretended on a 5-year follow-up (Oppen et al, 2005), and similar results were also shown in internet-based CBT with a 2 year follow-up (Andersson et al, 2014). The positive effect of CBT on obsessions and compulsions does not only remain at the individual level, but also in group therapies (Kearns et al, 2010;Safak et al, 2014), which is also shown in follow-up sessions (Haland et al, 2010). In the case of religious OCD, Abramowitz (2001) found a positive effect of ERP and/or cognitive intervention on religious OCD.…”
Section: Discussionmentioning
confidence: 79%
“…in two studies, approximately 41% to 45% of those who completed group cbt for ocd were classified as "recovered" based on measures of clinically significant change, compared with 62% to 63% of those who completed an individual modality (Anderson & rees, 2007;cabedo et al, 2010). open trials of group cbt for ocd show reductions of approximately 7 to 8 points on the y-bocs, or a 37% to 44% reduction, with a pre-post effect size of approximately 0.81 to 1.13 (Fenger, mortensen, rasmussen, & lau, 2007;Jónsson, hougaard, & bennedsen, 2009;Kearns, tone, rush, & lucey, 2010). this magnitude of change is somewhat lower than that of individual therapy for ocd, showing a change of about 10 to 15 points (houghton, saxon, bradburn, ricketts, & hardy, 2010).…”
Section: Other Treatment Modalitiesmentioning
confidence: 99%
“…It was limited in sample size and the patients were not randomly assigned. Also, the researchers have not collected data on further management[45]. However, it can be gathered from the study that group therapy is a handy way of delivering CBT with S. Bulut, M. Subasi Open Journal of Medical Psychology ERP especially because of lower drop-out rates.…”
mentioning
confidence: 99%